A biomimetic theranostic O2-meter for cancer targeted photodynamic therapy and phosphorescence imaging. (January 2018) - Li, Shi-Ying; Xie, Bo-Ru; Cheng, Hong; Li, Chu-Xin; Zhang, Ming-Kang; Qiu, Wen-Xiu; Liu, Wen-Long; Wang, Xiao-Shuang; Zhang, Xian-Zheng
Abstract: In this report, a biomimetic theranostic oxygen (O2 )-meter (cancer cell membrane@Pt(II) porphyrinic-metal organic framework, designated as mPPt) was constructed for cancer targeted and phosphorescence image-guided photodynamic therapy (PDT). mPPt presents high photosensitizers (PSs) loading and evitable self-quenching behaviors for favorable biological O2 sensing and PDT. Besides, endowed by the surface functionalization of cancer cell membrane, the homotypic targeting and immune escape abilities of mPPt could dramatically enhance its cancer targeting ability. Importantly, the O2 -dependent phosphorescence responsibility of mPPt could be employed to pre-evaluate the real time O2 level in situ and guide the PDT under light irradiation. A significant anticancer effect is observed after intravenous injection of mPPt and subsequent treatment with PDT with no obvious side effects. As a versatile platform for cell imaging, O2 fluctuation monitoring as well as PDT, this biomimetic O2 -meter exhibits great potential for biological analysis and personalized cancer theranostics. Graphical abstract: